Milieu-specific differences in symptom severity and treatment outcome in psychosomatic rehabilitation in Germany - Kleineberg-Massuthe, Henrika; Papst, Lilia; Bassler, Markus; Köllner, Volker (Frontiers in Psychiatry, 2023)
Introduction Previous studies that focused on socioeconomic differences did not comprehensively explain existing inequalities in psychosomatic rehabilitation in Germany. We applied a social milieu approach, which additionally includes sociocultural factors such as lifestyles, attitudes and values, to investigate differences among patients in symptom severity, psychosocial impairment and improvement over the course of the intervention. Methods As a model for social milieus, the empirical Sinus milieus were used. 2,000 patients of two psychosomatic rehabilitation clinics in Germany were included and their milieu was assessed with the Sinus milieu indicator for Germany 10/2018 questionnaire. BDI-II (N = 1,832) and HEALTH-49 (N = 1,829) questionnaires were used to measure depressiveness and psychosocial impairment at admission (T0) and discharge after 5 weeks of treatment (T1). Milieu differences in severity and improvement were analyzed by mixed-model ANOVAs. Results Milieu distribution was not representative of the overall population of Germany. We found significant differences between patients from different milieus in both BDI-II and HEALTH-49 (p < 0.001). Patients from the Precarious Milieu had the highest burden of depressive symptoms in BDI-II and the highest impairment on all HEALTH-49 scales at T0 and T1. Over the course of rehabilitation, patients from all milieus improved significantly in all domains (p < 0.001). Significant interaction effects showed milieu-dependent differences in improvement for depressiveness on the BDI-II [F(9, 1822) = 2.50, p = 0.008] and for three HEALTH-49 scales, namely Psychological well-being [F(9, 1819) = 3.30, padj = 0.005], Interactional difficulties [F(9, 1819) = 2.74, padj = 0.036] and Activity and Participation [F(9, 1819) = 4.94, padj < 0.001], while post-hoc tests only revealed two significant group differences for the last scale. In all domains, patients from the Precarious Milieu retained higher symptoms and impairment at T1 than patients from better-off milieus had at T0. Discussion Social milieu was associated with symptom severity, treatment access and outcome of psychosomatic rehabilitation patients. Milieu-specific sociocultural habits, psychosocial needs and therapeutic demands may help describe differences and should be considered in therapy planning and implementation, to improve equal access, quality and effectiveness of rehabilitation. Therefore, further research on milieu-specific differences and needs is necessary.